2000
DOI: 10.1021/ja9940064
|View full text |Cite
|
Sign up to set email alerts
|

Efforts toward the Expansion of the Genetic Alphabet:  Information Storage and Replication with Unnatural Hydrophobic Base Pairs

Abstract: The faithful recognition of the interstrand hydrogen bonds between complementary nucleobases forms the foundation of the genetic code. The ability to replicate DNA containing a stable third base pair would allow for an expansion of the information content of DNA by supplementing the existing two base pairs of the genetic alphabet with a third. We report the optimization of unnatural nucleobases whose pairing in duplex DNA is based on interbase hydrophobic interactions. We show that the stability and selectivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
192
0
11

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 188 publications
(209 citation statements)
references
References 36 publications
(96 reference statements)
6
192
0
11
Order By: Relevance
“…8,9,11,14,15,20,22,[28][29][30][31][32][33][34] From these, 60 were collected ( Figure 2) and their phosphoramidites incorporated into the 3' end of a 24-mer primer oligonucleotide and at the 24 th position of a complementary 45-mer template oligonucleotide. Hybridization of any given primer strand with any template strand results in an unnatural primer terminus (dX:dY, where dX is the primer nucleobase and dY is the template nucleobase).…”
Section: Screening For Unnatural Base Pairsmentioning
confidence: 99%
See 1 more Smart Citation
“…8,9,11,14,15,20,22,[28][29][30][31][32][33][34] From these, 60 were collected ( Figure 2) and their phosphoramidites incorporated into the 3' end of a 24-mer primer oligonucleotide and at the 24 th position of a complementary 45-mer template oligonucleotide. Hybridization of any given primer strand with any template strand results in an unnatural primer terminus (dX:dY, where dX is the primer nucleobase and dY is the template nucleobase).…”
Section: Screening For Unnatural Base Pairsmentioning
confidence: 99%
“…Indeed, several nucleotides bearing predominantly hydrophobic nucleobase analogs have been shown to pair stably and selectively in duplex DNA. 13,14 We, 9,10,15,16 and others, 8,12,[17][18][19] have shown that hydrophobic forces are also sufficient for the enzymatic synthesis of an unnatural base pair by incorporation of an unnatural nucleoside triphosphate against a template unnatural nucleotide; however, synthesis beyond the unnatural base pair, i.e. extension, tends to be relatively inefficient and generally limits the utility of these base pairs.…”
Section: Introductionmentioning
confidence: 99%
“…The creation of artificial nucleic acid motifs has relied on synthetic incorporation of nucleobases with altered hydrogen--bonding patterns 14,15 , or relying on hydrophobic interactions 16,17 and metal coordination 18--20 . Synthetic incorporation of unnatural bases which present more than one hydrogen--bonding 'face' in order to access higher--order DNA structures has been of great interest 21--25 .…”
mentioning
confidence: 99%
“…It has been possible to develop stable base pairs of this type, sometimes incorporated into DNA with high fidelity, but chain termination after insertion has been a significant problem (e.g. d3MN, dPICS and d7AI) [98,99]. Interestingly, the most efficient pairs have been "self-pairs," which is to say a base that elicits itself in DNA synthesis, which is perfectly reasonable for genetic code expansion.…”
Section: Recoding -Beyond Amber Suppressionmentioning
confidence: 99%